ACOUSTIC EMISSION MODEL WITH THERMOACTIVATIVE DESTRUCTION OF COMPOSITE MATERIAL SURFACE - Filonenko, Sergii (Proceedings of National Aviation University (archive), 2015)
A model of acoustic emission formation during machining of the composite material for the prevailing thermoactivative destruction of surface layer is represented. It is determined that the resulting acoustic emission signal is a continuous signal with the strongly broken shape. The dependences of the variation of the amplitude and energy of the resulting acoustic emission signal in time are obtained. It is shown that if process of composite material destruction is stable in a different intervals of analysis, stable values of amplitude characteristics of the resultant acoustic emission signal are observed.